Design, fabrication and testing of an equipment to measure deep percolation - Jollykutty Eapen (Department of Land and water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1990)
Because of the semi - aquatic nature, the water requirement of rice is 2 - 3 times greater than other crops. The measurement or prediction of percolation losses in field situation is of great practical significance for efficient irrigation and also for the determination of the nutrient losses. A precise knowledge of water requirement of crop attains importance for increasing production. The present investigation was taken up to design, fabricate and test an equipment to collect deep percolation water, quantify it and to assess the nutrient losses in the percolation water. The study was undertaken in ‘Mundakan’ season and the variety was ‘Triveni’. The location was the Instructional Farm of KCAET, Tavanur. The main source of irrigation water was filter point tubewell. Estimations of evaporation, transpiration and percolation were made on the basis of measurements using evaporimeter, evapotranspirimeter and field hook gauge. Vertical percolation was assessed using percolation – meter which was designed and fabricated for this study. Lateral percolation was obtained by subtracting vertical percolation from total percolation. The study revealed that the total water requirement was 1270.25 mm. The percentages of water lost by evaporation, transpiration, and total percolation are 13.69, 31.0 and 55.3. The water which is lost by vertical and lateral percolation are 59.4 and 40.6 per cent of the total percolation respectively. There was a gradual increase in the rate of evaporation during the initial stage. Then it decreased up to 65 days and then again increased up to the final stage. Rate of transpiration remained almost constant up to 10 days and then the rate slowly increased as the crop grew. The rate increased up to the booting stage. There was a gradual decrease in the rate of transpiration in the final stage. The rate of total percolation remained almost constant during the crop period. More than 50 per cent of the applied water is lost through percolation. During the initial stage, vertical percolation rate was higher than in the subsequent days. After 10 days, the vertical percolation rate remained almost constant. The rate of lateral percolation was constant during the crop period except in the sixth week after transplanting. The samples of percolation water were collected and the NPK losses due to deep percolation were analysed by the standard methods. The maximum percolation losses of applied NPK occurred on the first day of application and there was only traces from the fourth day onwards. Nitrogen and potassium losses were higher than the loss of phosphorus which was negligible. The NPK losses due to deep percolation is not much when compared to the run off losses. This may be due to the fact that the NPK content in the solution gets fixed in the soil as it percolates down through the soil. So the water that goes beyond the root zone will contain only very little NPK. The equipment fabricated for the measurement of deep percolation losses worked satisfactorily. Knowledge of water requirement of rice will greatly help in the efficient utilisation of available water.